Rare and everywhere: Perspectives on scale-free networks - Holme, Petter (Nat Commun, 2019)
Are scale-free networks rare or universal? Important or not? We present the recent research about degree distributions of networks. This is a controversial topic, but, we argue, with some adjustments of the terminology, it does not have to be.